Genes of renin angiotensin system and coronary heart disease - Ashavaid, T. F. (Springer India, 2000)
Coronary constriction, proliferation of smooth muscle cells and arrhythmia are involved in the pathophysiology of coronary heart disease and its complications such as myocardial infarction and sudden death. All these effects are favoured by high angiotensin II levels. Angiotensin II is the main effector molecule of the renin angiotensin system and it acts through angiotensin II type receptors. Genetically determined differences in the expression of the components of this system could adversely affect angiotensin II concentration and subsequently heart. Consequently each component of this system represents a potential candidate in the etiology of cardiovascular disease. In this article we review the variation of the angiotensin I converting enzyme, angiotensin II type I receptor and angiotensinogen genes and their association with cardiovascular disease.